Alzheimer's disease risk ABCA7 p.A696S variant disturbs the microglial response to amyloid pathology in mice - Xiaoye Ma; Dmitry Prokopenko; Ni Wang; Tomonori Aikawa; Younjung Choi; Can Zhang; Dan Lei; Yingxue Ren; Keiji Kawatani; Skylar C. Starling; Ralph B. Perkerson; Bhaskar Roy; et al. (Neurobiology of Disease, 2025)
The adenosine triphosphate–binding cassette transporter A7 (ABCA7) gene is ranked as one of the top susceptibility loci for Alzheimer's disease (AD). While ABCA7 mediates lipid transport across cellular membranes, ABCA7 loss of function has been shown to exacerbate amyloid-β (Aβ) pathology and compromise microglial function. Our family-based study uncovered an extremely rare ABCA7 p.A696S variant that was substantially segregated with the development of AD in 3 African American families. Using the knockin mouse model, we investigated the effects of ABCA7-A696S substitution on amyloid pathology and brain immune response in 5xFAD transgenic mice. Importantly, our study demonstrated that ABCA7-A696S substitution reduces amyloid plaque–associated microgliosis and increases dystrophic neurites around amyloid deposits compared to control mice. We also found increased X-34–positive amyloid plaque burden in 5xFAD mice with ABCA7-A696S substitution, while there was no evident difference in insoluble Aβ levels between mouse groups. Thus, ABCA7-A696S substitution may disrupt amyloid compaction resulting in aggravated neuritic dystrophy due to insufficient microglia barrier function. In addition, we observed that ABCA7-A696S substitution disturbs the induction of proinflammatory cytokines interleukin 1β and interferon γ in the brains of 5xFAD mice, although some disease-associated microglia gene expression, including Trem2 and Tyrobp, are upregulated. Lipidomics also detected higher total lysophosphatidylethanolamine levels in the brains of 5xFAD mice with ABCA7-A696S substitution than controls. These results suggest that ABCA7-A696S substitution might compromise the adequate innate immune response to amyloid pathology in AD by modulating brain lipid metabolism, providing novel insight into the pathogenic mechanisms mediated by ABCA7. One sentence summary: A rare Alzheimer's disease risk ABCA7 p.A696S variant compromises microglial response to amyloid pathology.